Current diagnosis & treatment : neurology - Brust, John C. M. (New York : McGraw-Hill Medical, 2019)
Practical, up-to-date strategies for assessing and managing the neurologic conditions most frequently seen in adults and children--
Section I: Neurologic investigations. Electroencephalography / Tina Shih; Electromyography, nerve conduction studies, & evoked potentials / Dora Leung; Neuroradiography / Maria J. Borja & John P. Loh. Section II: Neurologic disorders. Coma / John C.M. Brust; Aphasia, apraxia, & agnosia / John C.M. Brust; Hearing loss & dizziness / Jack J. Wazen, Soha N. Ghossaini & Benjamin J. Wycherly; Epilepsy & seizures / Tina Shih; Headache & facial pain / Mark W. Green & Anna Pace; Dementia & memory loss / Karen Marder ... [et al.]; Cerebrovsascular disease: ischemic stroke & transient ischemic attack / Joshua Z. Willey; Cerebrovascular disease: hemorrhagic strokes / Richard A. Bernstein & Philip Chang; Central nervous system neoplasms / Christopher E. Mandigo & Jeffrey N. Bruce; Paraneoplastic neurologic syndromes / Ugonma N. Chukwueke ... [et al.]; Trauma / Katja E. Wartenberg & Stephan A. Moyer; Movement disorders / Blair Ford & Susan B. Bressman; Ataxia & cerebellar disease / Harini Sarva & Clair Henchcliffe; Multiple sclerosis & demyelinating diseases / Bruce A.C. Cree; Nontraumatic disorders of the spinal cord / Olajide Williams, Jared Levin & Michelle Stern; Peripheral neuropathies / Thomas H. Brannagan III; Motor neuron diseases / Neil A. Shneider & Michio Hirano; Autonomic disorders / Louis H. Weimer; Myasthenia gravis & other disorders of the neuromuscular junction / Svetlana Faktorovich & Shanna K Patterson / Diseases of muscle / Christina M. Ulane & Olajide Williams; Mitochondrial diseases / Michio Hirano; Neurologic intensive care / Santiago Ortega-Gutierrez & Alan Z. Segal; Bacterial, fungal, & parasitic infections of the nervous system / Barbara S. Koppel, Kiran T. Thakur & Adedoyin Akinlonu; Viral infections of the nervous system / Kiran Thakur & James M. Noble; HIV neurology / Deanna Saylor ... [et al.]; Prion diseases / Lawrence S. Sonig; Disorders of cerebrospinal fluid dynamics / John C.M. Brust; Sleep disorders / Andrew J. Westwood & Carl Bazil; Systemic & metabolic disorders / Laura Lennihan & Jason Diamond; Alcoholism / John C.M. Brust; Drug dependence / John C.M. Brust; Psychiatric disorders / Eric R. Marcus; Neurologic disorders of childhood & adolescence / Cladduai A. Chiriboga & Marc C. Patterson.
"A Lange medical book."
Description based on publisher supplied metadata and other sources.
Keywords: Nervous system -- Diseases -- Diagnosis